A bateria na performance musical do forró - Dantas, Gledson Meira (2024)
In this work we deal with two conventional universes and all the complexity that orbit them, namely, the musical universe of the drums, and all the conventions at their most diverse levels, and the universe that contemplates forró, with emphasis on this as a musical genre, and focus on its “traditional” aspect, which was treated in this work as “forró gonzaguiano”. The studies revealed the multiple faces, characteristics and possibilities of both instrumental interpretations and aspects of this musical genre, demonstrating the complex, plural and broad nature of these two worlds. At this juncture, this work analyzes and reflects on the interpretation of the drums in the musical performance of forró, based on the work of Dominguinhos. The methodological basis of the work consisted of bibliographical research and documentary research, with an emphasis on “phonographic research”. From bibliographical research, the epistemological and theoretical dimension of the work is based, above all, on studies about genre and musical style, instrumental interpretation and musical performance, articulating areas such as musicology, ethnomusicology and sociology. The approach to musical performance understood in this work, in addition to contemplating the views and perceptions that give importance to the specificities, characteristics and nuances of instrumental praxis, understands this as a process that encompasses both these technical-structural issues, as well as the processes of social interaction and production of experiences. The interpretations and reflections discussed in this paper support the thesis that what constitutes the interpretation of the drums in the musical performance of forró gonzaguiano comprises a set of aspects that are related and interact with each other, which are based on two dimensions directly linked to the musical universe, namely, 1) the technical capacity and mastery related to the praxis of the drums, 2) the understanding of the nuances and characteristics that underpin and legitimize the musical genre. Despite not having conducted interviews with the drummers, we can infer, since this is a human relational activity, that, most likely, in addition to these two dimensions, the reading of the world and music incorporated in the drummer through his experiences, interactions and formative processes as a social subject and musical agent, with this last aspect being responsible for giving the differentiation in the color of each musical screen. In other words, the diversity of ways and paths of interpreting the drums in a forró musical performance is associated with a set of standards and conventions that need to be followed. However, this diversity, as it is infected by different habitus, incorporated and constituted in the drummer agents, who have different experiences and relationships with the context and universe of forró and drums, will make them produce different forrós.